Tunable dielectric metamaterial based on strontium titanate artificial atoms. (15th July 2020) - Liu, Xiaoming; Ren, Zhiyu; Yang, Tian; Hao, Yanan; Wang, Qiang; Zhou, Ji
Abstract : Metamaterials are designed and manufactured artificially to manifest intriguing physical concepts and achieve unusual potential applications. However, the exotic properties of metamaterials normally originate from the resonance mechanism of artificial atoms, thus inevitably limited in narrow band and hindering their practical applications. Here, we numerically design and experimentally verify a novel tunable dielectric metamaterial based on strontium titanate artificial atoms to alleviate the bandwidth restriction of resonance metamaterial. By control of the magnetic resonance with the electric resonance, the tunable dielectric metamaterial can broaden the practical applications of metamtaterials and play an important role in all-optical communication devices. Graphical abstract: Image, graphical abstract